STUDY OF THE STRESS-DEFORMED STATE OF THE HIP JOINT MODEL IN CHILDREN UNDER THE CONDITIONS OF DYSPLASIA AND CONSERVATIVE TREATMENT - Onischenko, О.V.; Korolkov, O.I.; Ksonz, I.V.; Karpinskyi, M.Yu.; Yaresko, О.V. (World of Medicine and Biology, 2021)
In this work, a comparative study of the stress-strain state of the elements of the hip joint in children in normal and in the case of its dysplastic changes in the application of the technique of "trampling" used for conservative treatment of hip dysplasia. To solve this goal, several mathematical models of the child's hip joint were built using the finite element method. In the process of constructing the calculation model, the geometric model of the pelvis-thigh was taken as a basis, which is based on the method of creating a model of geometric sections obtained from tomographic images. As a result of the conducted mathematical research significant changes in the nature of the stress-strain state in normal and dysplastic hip joint using the technique of "trampling" in comparison with previously obtained data for single-support standing, which, in our opinion, may be one of the significant factors joint in the process of conservative treatment. The obtained data should contribute to the definition and optimization of methods of additional mechanical stimulation of the components of the hip joint for its normal development during treatment.
Keywords: hip joint; dysplasia; child; biomechanics; acetabulum